2023
DOI: 10.1155/2023/1678226
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Virtual Reality Technology on Jordan’s Learning Environment and Medical Informatics among Physicians

Abstract: The purpose of this study is to look into the components that affect the behavioral intention of Jordanians to use Virtual Reality Technology in the Learning Environment (VRTLE). For the educational and entertainment industries, virtual reality presents both obstacles and opportunities. The goal of this study is to determine the factors that influence VRTLE acceptance and to propose how such technology may be integrated into the educational setting of students and universities. A total of 60 students from priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In many different types of educational settings, the utilization of Vir tual Learning Environments is advantageous [19][20][21][22]. Despite this, it has drawbacks such as an absence of trust, decreased group interaction, social separation, and concealed scientific costs.…”
Section: Problem Statementmentioning
confidence: 99%
“…In many different types of educational settings, the utilization of Vir tual Learning Environments is advantageous [19][20][21][22]. Despite this, it has drawbacks such as an absence of trust, decreased group interaction, social separation, and concealed scientific costs.…”
Section: Problem Statementmentioning
confidence: 99%
“…It was found that performance expectancy was the primary criterion which influence retailers' behavioral intention to adopt mobile payment apps [39]. The studies [40][41][42][43][44][45][46][47] have also studied the relationship between performance expectancy and behavioral intention. With this backdrop, the following hypotheses were formed: H1: there is no impact of performance expectancy on behavioural intention to use mobile payment applications.…”
Section: Introductionmentioning
confidence: 99%
“…In research conducted by Alshare and Lane [55], it was revealed that there is a strong relationship between effort expectancy and the behavioral intention of customers. The studies [40][41][42][43][44][45][46][47] have also evaluated the relationship between effort expectancy and behavioral intention. The above discussion led to the formulation of the following hypothesis: H2: there is no impact of effort expectancy on behavioral intention to use mobile payment applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation